Problem of spreading fake information in the Internet space analysis - T. N. Kameneva; A. V. Kulchitskiy; S. A. Kotlyarov; M. Yu. Kazaryan; E. S. Orlova (Цифровая социология, 2023)
Modern Internet space is filled with various kinds of information, including unreliable, fake information. In the current socio-cultural, socio-political, and socio-economic conditions, we should expect further increase in the spread of fakes and, as a consequence, their negative impact on people’s lives. The article analyses results of a sociological study on the attitude of the Kursk region population to fakes spread in the Internet space. The empirical basis of the study is the results of the online questionnaire survey conducted in September 2022 in the Kursk region. The sample population of the study was 521 people living in the territory of Kursk and Kursk region. Fakes are becoming a real part of life in modern society. Residents of the region are constantly faced with inaccurate information. They recognize its danger and note that fakes nevertheless “attract” their attention. The current situation requires additional measures development to regulate dissemination of information in the Internet space.